HOUT-15. IDENTIFICATION AND CHARACTERIZATION OF CARDIAC EVENT ABNORMALITIES IN PATIENTS WITH CRANIOPHARYNGIOMA. (11th November 2019) - Seligman, Christa; Harrison, Rebecca; Hassan, Saamir; Wu, Jimin; DeGroot, John; Raza, Shaan
Abstract: BACKGROUND: Craniopharyngiomas (CP) are frequently associated with a malignant clinical trajectory despite their benign histology. This population frequently has endocrinopathies and autonomic dysfunction due to tumour location, which may influence cardiac function and long term health outcome. In this study, we evaluated for clinical and paraclinical cardiac abnormalities in adult and pediatric patients with craniopharyngioma. METHODS: We retrospectively identified patients in our neurosurgery database with a diagnosis of craniopharyngioma that received neurosurgery at MD Anderson Cancer Center. We queried the medical record for demographic and disease-related information, as well as clinical information regarding cardiac risk factors. Perioperative electrocardiograms (EKGs) were analyzed where available. RESULTS: We identified 56 patients with craniopharyngioma, 27 (48.2%) of which were female. Average age was 39 years, and all patients had undergone subtotal (49.1%), gross total (32.7%), or near gross total (18.2%) resection. Over half (53.6%) had undergone radiation, none had received systemic therapy, and 1 (1.8%) intra-cystic chemotherapy. The majority had adamantanomatous-type histology (83%) and the remainder papillary (17%). At diagnosis, average BMI was elevated at 30.98. Hypertension (30.4%), diabetes mellitus (32.1%), and thyroid dysfunction (80%), were found in this cohort. Nearly a quarter (23.2%) were on statin therapy for dyslipidemia. Stimulant (14.3%) and neuropleptic (3.6%) use were also identified. Of patients with perioperative EKG performed (N= 39), 30 were available for review. Of these, patients were identified with abnormal rate (N=9, 30.0%), PR interval (N=2, 6.7%), QRS interval (N=4, 13.3%), and QTc interval (N=1, 3.3%). Some patients presented with a history of heart palpitations (1.8%) and syncopal episodes (3.6%), but not chest pain. CONCLUSION: This analysis demonstrates frequent vascular and cardiac risk factors in patients with craniopharyngioma. We advocate for increased awareness of cardiac health in this young population. Further prospective evaluation is warranted to better understand cardiac health in this patient group.